Is a chest pain observation unit likely to be cost saving in a British hospital? - Goodacre, S. (BMJ Group, 2001)
Background—Studies from the United States (US) suggest that using a chest pain observation unit (CPOU) saves from $567 to $2030 per case compared with hospital admission. These savings will only be reproduced in the United Kingdom (UK) if the cost of routine hospital admission is similar. This study aimed to review current practice to determine the proportion of patients suitable for CPOU evaluation, the cost per case of routine admission and compare this with control groups in US studies. Methods—300 patients were randomly selected from those admitted with chest pain between January and June 1998. Two independent observers reviewed the case notes to determine who would have been suitable for CPOU management. Resource use of those selected was then determined. Results—Notes were retrieved for 285 patients. A total of 106 (37.2%) were suitable for CPOU care. Mean length of stay was 51 hours (median 24). Only two patients were admitted to the coronary care unit. Interventional cardiology was limited to two angiograms, one angioplasty and one bypass graft. Estimated mean cost per patient was £458 ($733) with interventional cardiology included, £356 ($570) without. Conclusion—Potential exists for the introduction of CPOU care to reduce health service costs in the UK. However, the magnitude of cost savings demonstrated in US studies were achieved by comparison to relatively high inpatient costs and should not be extrapolated. Economic evaluation of the CPOU should be repeated in the UK. The inclusion of interventional cardiology costs is an important determinant of cost effectiveness.